Design, synthesis, and antitumor activity of novel paeonol derivatives containing the 1, 4-benzoxazinone and 1, 2, 3-triazole moieties. Issue 7 (July 2019) - Yang, Tingting; Shi, Xin; Guo, Libing; Gu, Shaohua; Zhang, Weiwei; Xu, Guiqing; Li, Wei; Jiang, Yuqin
A new series of paeonol derivatives containing the 1, 4-benzoxazinone and 1, 2, 3-triazole moieties were synthesized and evaluated for their cytotoxicity in vitro against human non-small cell lung cancer NCI-H1299 cells and human cervical carcinoma HeLa cells. Among them, compared with that of paeonol, compounds 8-acetyl-4-{[(1-(5-chloro-2-nitrophenyl)-1 H -1, 2, 3-triazol-4-yl]methyl}-5-methoxy-2 H -1, 4-benzoxazin-3(4 H )-one,  8-acetyl-4-[(1-mesityl-1 H -1, 2, 3-triazol-4-yl)methyl]-5-methoxy-2 H -1, 4-benzoxazin-3(4 H )-one, and 8-acetyl-5-methoxy-4-{[(1-(naphthalen-1-yl)-1 H -1, 2, 3-triazol-4-yl]methyl}-2 H -1, 4-benzoxazin-3(4 H )-one exhibited significant inhibitory activity toward the human non-small cell lung cancer NCI-H1299 cells (IC50  = 13.36 ± 0.003, 19.75 ± 0.3, 15.79 ± 0.05 μg mL −1 ). The last compound also exhibited significant inhibitory activity toward the human cervical carcinoma HeLa cells (IC50  = 19.73 ± 1.0 μg mL −1 ).